Hubungan antara Efikasi Diri dengan Sikap Pengasuhan Digital: Kajian pada Orang Tua Marginal - Irni Prihardini; Riana Sahrani; Fransisca Iriani Roesmala Dewi (Humanitas (Jurnal Psikologi), 2024)
The high use of the internet and digital devices among children in Indonesia is generally not accompanied by adequate supervision and rules from parents. This can create a gap between the parenting provided and what children receive through digital devices and the internet. Digital parenting has become essential for parents to implement appropriate parenting strategies that align with their roles and responsibilities in the digital era. Digital parenting attitudes encompass the cognitive and emotional aspects of parents toward their children's use of digital devices and media. One factor that can enhance digital parenting attitudes is parental self-efficacy, referring to parents' beliefs and competencies in managing their children's use of digital technology. This study aims to understand the role of digital parenting self-efficacy in shaping digital parenting attitudes. The research employs a non-experimental quantitative method with convenience sampling, using correlation and regression analysis. The instruments used are the Digital Parenting Attitude Scale and the Digital Parenting Self-Efficacy Scale. The study involved 385 stay-at-home mothers with elementary-aged children who do not work and live in marginalized areas. The results indicate that self-efficacy in digital parenting plays a role in shaping parents' digital parenting attitudes.